Two- and Three-Dimensional Echocardiography for Primary Cardiac Lymphomas: A Case Report and Literature Review - Huan Cen, MS, Jinhua Li, MD, Bijing Li, MS, Pengtao Sun, MS (Advanced Ultrasound in Diagnosis and Therapy, 2020)
Cardiac lymphomas have an extremely low incidence, with primary cardiac lymphomas accounting for only 0.5% of all extranodal lymphomas and 2% of primary cardiac tumors. Early diagnosis is critical for these tumors, which can proliferate rapidly. Here, we report a rare case of a 66-year-old man with primary cardiac lymphomas in the right atrium and right ventricle. This case establishes that two- and three-dimensional echocardiography is instructive in establishing the relationship of the mass and surrounding tissues and providing relevant hemodynamic information.